Politična geografija globalizacije - Bufon, Milan (Geografski vestnik, 2006)
The first part of the article discusses some basic features concerning the definition of globalization and its effects. It also presents some current issues of globalization in relation with some key drivers of political geographical transformations. The latter are more visible in particular on the field of international politics and security, as well as on the field of international commercial and financial flows. On the basis of the discussed development processes, the article finds that political geographical problems of globalization are closely linked also to the question of concentration and deterritorialization, and the world central-peripheral relations. Globalization then influences political, economic and social balances and interactions between the local, statal and global dimension of development potentials and dynamics, and the possibility of enhancing global governance structures.
Keywords: politična geografija; geopolitika; svetovna politika; mednarodna varnost; mednarodna trgovina; globalizacija; globalization